What's so special about special education? - Merrow, John.; O'Riordan, Karena; Slutsky, Sonia; Learning Matters, Inc.; PBS Home Video ([New York, N.Y.] : Learning Matters, Inc., [Alexandria, Va.] : Distributed by PBS Home Video, 1995)
"This program follows two disabled girls through a year of Denver's public school system to test the progress of special education, and asks the question- how well are we educating disabled students in public schools?"--Container.
DVD.
Announcer, Tom Clark.
Editor, Daniel J. Bernstein ; music, Mark Degliantoni.
"Premiered on PBS in 1996"--Container.
"A federal law passed in 1975 allowed disabled children into regular public schools, signaling a revolution in special education. Twenty years later, public schools enrolled over 5 million special education students, at a price tag of over $30 billion. But does access to regular classes ensure an equal -- or even adequate -- education?"--Container.
Keywords: Special education -- United States; Special education schools -- United States; Special education schools -- Colorado -- Denver; Special education -- Law and legislation -- United States; Public schools -- Colorado -- Denver; United States; Documentary videos